PROSES KOMUNIKASI KADER PKK DALAM MENGHADAPI HOAKS INFORMASI KESEHATAN PADA ERA POST TRUTH - Hadisiwi, Purwanti; Suminar, Jenny Ratna; Prasanti, Ditha (Master of Communication Science Program, Universitas Diponegoro, 2021)
This research article is the result of research conducted on PKK cadre teams in Bandung, Sumedang, and Banjar districts. When hoaxes and health information become studies that have an impact on people's lives, it seems like something normal. In fact, who would have thought that the hoax of health information could have fatal consequences for some people, especially in the case of this article being reviewed is the PKK cadre team in the area. Another interesting thing is that the hoax of health information was felt by cadre mothers recently, more precisely during the post truth era. This phenomenon becomes interesting to be studied in depth, therefore the authors describe the findings from observations and interviews in the field. The findings generated in this study are; 1) the hoax health information spreads quickly so that it is difficult for cadre mothers to distinguish and confirm the accuracy of the information; 2) there were some female cadres who were trapped in the hoax of health information and then practiced what was conveyed in the hoax information; 3) the communication process carried out by the cadre mothers in dealing with the hoax of health information can be described starting from the communicator, messages, communicants, and the effects felt by the cadre.